Exogenous melatonin enhances heat stress tolerance in sweetpotato by modulating antioxidant defense system, osmotic homeostasis and stomatal traits - Sunjeet Kumar; Rui Yu; Yang Liu; Yi Liu; Mohammad Nauman Khan; Yonghua Liu; Mengzhao Wang; Guopeng Zhu (Horticultural Plant Journal)
Heat stress hinders the growth and productivity of sweetpotato plants, predominantly through oxidative damage to cellular membranes. Therefore, the development of efficient approaches for mitigating heat-related impairments is essential for the long-term production of sweetpotatoes. Melatonin has been recognised for its capacity to assist plants in dealing with abiotic stress conditions. This research aimed to investigate how different doses of exogenous melatonin influence heat damage in sweetpotato plants. Heat stress drastically affected shoot and root fresh weight by 31.8 and 44.5%, respectively. This reduction resulted in oxidative stress characterised by increased formation of hydrogen peroxide (H2O2) by 804.4%, superoxide ion (O2•−) by 211.5% and malondialdehyde (MDA) by 234.2%. Heat stress also reduced chlorophyll concentration, photosystem II efficiency (Fv/Fm) by 15.3% and gaseous exchange. However, pre-treatment with 100 μmol L−1 melatonin increased growth and reduced oxidative damage to sweetpotato plants under heat stress. In particular, melatonin decreased H2O2, O2•− and MDA by 64.8%, 42.7% and 38.2%, respectively. Melatonin also mitigated the decline in chlorophyll levels and improved stomatal traits, gaseous exchange and Fv/Fm (13%). Results suggested that the favorable outcomes of melatonin treatment can be associated with elevated antioxidant enzyme activity and an increase in non-enzymatic antioxidants and osmo-protectants. Overall, these findings indicate that exogenous melatonin can improve heat stress tolerance in sweetpotatoes. This study will assist researchers in further investigating how melatonin makes sweetpotatoes more resistant to heat stress.